Hilda Olsonin hämähäkkiakvarellit vuosilta 1859-1862. - Talman, Ritva (2012)
Tieteellinen artikkeli
Tahiti 2/2012
Internet-yhteys; www-selain.
jufo:0
Keywords: Olson, Hilda; akvarellimaalaus; hämähäkit; akvarellmålning; spindlar